Creating Secured Residential Places: Conflicting Design Elements of Natural Surveillance, Access Control and Territoriality. (October 2019) - Seifi, M; Abdullah, A; Haron, S; Salman, A; Seifi, M
Abstract: Territoriality, natural surveillance and accesses control are the preeminent strategies of most place-based crime prevention theories and practices. They have been extensively applied as non-detachable part of defensible space and Crime Prevention Through Environmental Design (CPTED). Even though, a large body of knowledge confirms the effectiveness of these three strategies in preventing residential burglaries, yet, they frequently diminish each other's effect. Besides, there are divergent views about their implementation, which often brings about contradictory designs and planning decisions, all of which have left architects and planners with a state of ambiguity on hiring felicitous physical elements which prevent burglaries. Hence, the current paper aims to find the design elements of the CPTED strategies which are in conflict in creating security. The study employs the qualitative method of systematically reviewing and critically analysing the literature on the subject. Conjointly, the physical features and design elements of natural surveillance, access control, and territoriality are extracted from the evidence in the literature. The results of the analysis show that the design elements of natural surveillance and access control are more recognized and employed since they are easier to understand as compared to territoriality. Furthermore, it was found that some of the physical elements of access control territoriality conflict with surveillance design elements or diminish the effects of natural surveillance on burglary prevention. Conversely, the social aspects of territoriality design strengthen the effects of natural surveillance. Therefore, the study concludes that the burglary prevention design should consider all the strategies simultaneously. Hence, it is recommended to combine the physical aspects of natural surveillance and access control with the social aspects of territoriality for successful burglary prevention. This study contributes to the body of knowledge related to CPED by shedding light on the deployment of its main strategies without conflict in their effects. However, there is a need for furthered evidence of the design elements of natural surveillance, access control, and territoriality. Only a thorough examination and comparison of the impacts of their design elements on a residential burglary in a single context could further confirm the literature findings of the present study.